Kentsel Tasarım Elemanı Olarak Bitkilendirme İle İklim Kontrolü : Bağdat Caddesi, I. Levent Ve Ataşehir Örneği - Bostancı, Yasemin (Fen Bilimleri Enstitüsü, 1998)
Çevre ; insan yaşamının oluşturduğu ilişkiler ortamının tümüdür. İnsan yaşadığı mekanla birlikte çevreye bağımlıdır. Toplumu oluşturan bireylerin sağlıklı bir çevrede, teknik, ekonomik, sosyal, kültürel ve estetik değerlere sahip, çağdaş bir yaşam düzeyine ulaşmasında ise en önemli unsurlardan biri planlamadır. Şehir planlamanın belirli bir çalışma alanım içeren kentsel tasarımda amaç ; insana en iyi yaşam koşullarını sağlamaktır. Kentin dokusunu oluşturan öğelerin bütününü, iklimsel koşullar, topoğrafık yapı, ekonomik ve sosyal yapı ve anlayışa, toplumun sahip olduğu teknolojiye bağlı olarak en iyi şekilde işlevlerine uygun düzenlemek için kentsel tasarım elemanlarının doğru kullanımıyla belirli Ölçülerde fiziksel çevre ve aynı zamanda iklim kontrolünü sağlamak mümkündür. Gelişen teknolojiye paralel olarak yaşam standartlarının yükselmesi, tasarım çalışmalarında bitkilerin görsel ve estetik değerlerinin yanısıra diğer yararlarını maksimum kullanıma yöneltmiştir. Kentsel tasarım elemanı olarak bitkiler, gürültü ve hava kirliliğini kısmen kontrol etmelerinin yanısıra iklim üzerinde de oldukça olumlu etkilere sahiptir. Bitkilerin amaca uygun tasarımım gerçekleştirmek için ise, farklı iklim bölgelerine göre tür ve yer seçimi yapılmalıdır. Güneş ışınımı, rüzgar, yağış ve nem gibi iklimsel faktörleri kısmen istenilen konfor düzeyine getirmek, bitkilerin ancak doğru ve bilinçli düzenlemesiyle gerçekleşir. Tezin konusunu oluşturan kentsel tasarım elemanı olarak bitkiler, 6 bölümde incelenmektedir : Bölüm l'de konuya giriş yapılmaktadır. Bölüm 2 'de tasarım, kentsel tasarım ve kentsel tasarım elemanı olarak bitkilere değinildikten sonra, Bölüm 3 'de bitkilerin fiziksel çevresine etkileri anlatılmaktadır Bölüm 4'de iklimsel faktörler ve iklimsel konforun sağlanması için bu faktörlerin bitkilerle kontrol edilme yöntemleri ile ilgili olarak bilgi verilmektedir. Bölüm 5 'de, İstanbul iklim bölgesine ait Bağdat Caddesi'nde yol boyunca, ayrık nizam yerleşim alam 1. Levent' de bina çevresinde ve serbest düzen Ataşehir toplukonut alanında açık mekanlarda bitkilendirme, iklim kontrolü açısından incelenmekte ve fotoğraflarla uygulamadaki olumlu veya olumsuz yönler irdelenerek öneriler yapılmaktadır. Bölüm 6'da ise konu ile ilgili sonuç ve değerlendirmeler yer almaktadır. özet olarak ; kentsel tasarım elemanı olarak bitkilerin amaca uygun olarak tesis edilmesi bilinçli bir düzenlemeyle olabilir ve bu da ancak bu konuda uzmanlaşmış kişilerin tasarımıyla gerçekleşir.

Climate Control With Plantation As An Urban Design Element Environment which is the consist of the relations created by human life, is also a scene for the happenings and changes for the social life. Human being, should work to meet the new and modern requirements which occure by science, technology developing contemporary life. So, human being needs to change his environment and create the man-made environment by using natural environmental sources. Human is depended to his environment with the space lived in. Planning is the main element to reach the contemporary life standards which has technical, economical, social, cultural and aesthetical values for human environments. City planning pays attention to provide social, economical and physical requirements of urban space. Urban design which is the certain branch of city planning, interests not only physical order of environment but also psychological requirement of environment users. The goal of urban design is to provide the best life condition for human. Physical environment and also climate is possible to control with correct using of urban design elements. Plants have an important role on studying the urban design. Each plant species has different growing properties and height. So plantation should be located by taking consideration the properties and plant species should be sellected according to its function. Plants as an urban design element may be indicated in 3 main design groups ;. Ceiling element (top cover) ; trees, understory. Vertical space divider ; shrub. Flat element (flat cover) ; meadow, grass, flowers Trees using for ceiling element are divided into four groups according to their shapes ;. Trees with large canopy. Trees with sharp pointed. Trees with column shape . Trees with pendulous shape Trees are divided into two groups according to type of their leaves ;. Broad-leaved trees (they fall their leaves in winter). Needle-leaved trees (they do not fall their leaves in winter) In design, plant species used for vertical space divider, is generally shrub. Shrubs specially make a connection between flat and ceiling. Plants as flat cover is a main green element which other plants placed on. Plant as an urban element, controls condition of climate which is consist of humidity, sun, solar radiation, wind, precipitation and also is used to improve the physical environment condition such as noise, air pollution. The effect of plant on physical environment are hereunder ; 1. View Control The plants which have a big potential with natural properties are important urban design elements due to visual and aesthetical effect. Moreover the volume, shape, texture and colour of plants are also important. In urban design, the goals of view control by using plants are described as hereunder ;. Providing visual attractiveness. Accenting of view. Hiding the undesired view. Providing privacy. Hiding control 2. Noise Control Noise is an unwilling sound which disturbs human and effects the health. In last decades, noise which was examined in the subject of environment pollution, was started to accapted as an echological property and described as a noise pollution which is a special type of air pollution. It is possible that noise pollution is partly prevented by using plants. According to researchs, green belt with 10 m. wide is able to reduce noise in measurable specs. Furthermore it is defined that tree screen which has shrubs at the bottom with 6.3 m wide in one row, even reduces noise effectively. 3. Cleaning Dirty Air and Providing Fresh Air Air pollution is a situation of spoiling air composition with mixing the foreign material in atmospheric air. Air pollution effects the health of living things and causes material damage.increasing of air pollution with paraleli to urbanization is mainly prevented by plants which are major atmospheric cleaner source. Green areas specially plantation with trees and forests have positive effects on preventing the air xvi pollution and providing clean air. The effect of plantaion is summarized into three groups.. They provide air circulation and flow in cities. They act like a filter and catch the solid particules and aerosels in air. They provide clean air by producing 02 for whole living things. In addition to noise and air pollution control, plants also adjust air temperature, as acting regulator. Today, it is possible that inside building light, moisture and temperature are adjusted at desired rates with mechanical devices. But in open spaces, this kind of regulation is not possible, so, plantation used for regulation the temperature in natural environmental. The researchs shows that since the time of ancients mans entire pattern of life was dependent upon the climate condition which he finds himself. Climate is pronounced impact on human physiology and temperment. The climate is result of light, temperature, moisture, precipitation and air movement and wind. The goal of urban design is to provide/create the best life condition for human. Suitable and comfortable physical environment condition should be formed depending on sun which is the main source of climate. Climate comfort is the condition of which human spends minumum energy to adapt to his environment. The climate control with plantation is hereunder ; 1. Solar Radiation Control Sun is major source that gives light and heat to earth. Basically plantation controls the sun effect by filtration of the direct solar radiation by control of grand surface and has the amount of heat radiated from these vaious surfaces, either daily or seasonally through the alteration of the ground temperature, through control reflected radiation and through total or major obstruction of the solar radiation itself. Trees and other green areas in cities balance the air temperature by controlling solar radiation. Leaves prevent/catch, reflect, absorb and transmit certain amount of sun rays. These effects depend on plant species, dense of leaves, shape of leaves, branch pattern. Deciduous trees will screen out direct sunlight, during summer to reduce required cooling loads, but allow it to pass through in the winter reducing reguired heating loads. There are important discrepancies consideration of temperature between bare area and plant cover area. Plant changes air temperature of the space by aborbing incoming solar radiation, preventing heat loss and controlling air movement. Geiger (1957) indicated that if a dense forest cover absorbs 75-80% of solar radiation and transmits about 5%, it reflects 15-20% a little less than reflection from meadow and grainfields. xvu 2. Shading Effects Of Plants Any trees selected should be suitable ecologically to the area. The designer can consider for deciduous trees, how long they are in leaf and how transparent they are to solar radiation, both in leaf and bare. Trees and other plants are growing active objects whose shadows change as the plant matures and undergoes essential changes in foliage. Thus it is more complicated to predict the shadows of trees. The key is to use the maximum characteristics of a tree. (It is height and crown at maturity) to determine its potential effect on solar access. Mature tree characteristics will be based on the maximum height of typical members of a species. Here are some special characteristic of trees that must be considered.. Mature height of trees of species. Mature diameter of tree crown. Seasonal variations in foliage, taking into account the distinction between the deciduous species (most of which shed leaves in fall) and evergreens (most of which do not). The distance from the ground to the crown C.A. Federer, in his paper on "The Effect Of Trees In Modifying Urban Microclimate" has this to say about the microclimate effect of trees. "The most obvious microclimatic effect of a tree is shade. Trees absorb and reflect solar radiation. The importance of solar radiation to the energy balance of an individual is demonsrated by the way we seek shade in hot weather and sun in cold weather. Evergreen trees provide shade year around ; the deciduous trees have an appropriate seasonal variation ; shade in summer and least partial sun in winter. Buildings also provide shade but it is only where tall buildings are already crowded closed together that increased shading by trees would not be a welcome benefit in summer". A tree concerning to its height and largeness and its distance to the space which is desired to be shaded, will effect its shade amount. For plantation a space, to the below mentioned general rules should be paid attention.. The maturity height of selected tree species should be paid attention. The wide of the crown cover should be paid attention. For a specific/determined space a suitable tree species, deciduous or coniferous trees should be sellected. Section, plan or graphics which show the shading pattern of trees should be used. At the zone effected by winter wind coniferous trees should be planted at the north of the buildings. Suitability of placing the tall trees far from the building and short trees closed to the building should be paid attention. xviu 3. Wind Control Wind is one of the most important factor which effect the human comfort. Wind efects the rate of comfort negatively or positively according to existence or non- existince plant covers at public space. One of the main factor by which microclimate is deliberately modified is by the use of trees provide shelter. The composition, structure and shape at a windbreak will depend on its particular purpose. A windbreak can reduce wind in two ways : the air which flows paraleli to the ground is defected up and over the belt and its speed is conseqently reduce by the factional drag and the eddies that occour in contact with the surface of trees ; and air flow is slowed down its passage through a stand of trees. To control the velocity of wind depends on features of the windbreak. These features are explained as follows :. Penetrability : The penetrability of a windbreak is directly its dense. For an optimum density ratio of a windbreak is 50-60%. Leaves, branches, foliages and trunck should cover 60% front area of windbreak. Norrow windbreak with mentioned dense will protect as much as wide windbreak with same dense.. Height : The ratio 1 :30 is accepted between height of windbreak and protected leeward zone. The distance that wind protection extends from the windbreak's leeward side is directly proportional to its height. The most effective zone of protection extends to a distance of 6 to 8 times its height, although some protection does extend to a distance of 20 times the height. A good windbreak should reduce the wind velocity by half for distances upto 10 times the height. The general distance allowance between the windbreaks and area to be protected should be 100 to 150 ft (no more than 300 ft).. Wideness : The wideness of windbreak has an effect upon protected area in two ways ; first one, is penetrability will be decrease with the increasing of wideness and protected area will be reduce, and second is the effect upon wind celocity. Caborn stated that protected area reduces with wide windbreaks, and wind directs downward with a high speed after passing the windbreak. And if a windbreak is narrow, the penetrability will increase so protected area will also reduce.. Length : Research shows that the lines of equal wind velocity have tendency to deviate toward the center of the barrier in the area of protection afforded by windbreaks, and adapt courses paraleli to it. An extension of the barier changes nothing except that the zones of isotacts paraleli to it are widened. The most efficient ratio of height to length for windbreak is 1:1 1.5.. Spacing : Spacing between trees and between tree rows is cratical to the health of the windbreak. A general rule is the wider the initial tree spacing, the longer the affective life of the windbreak. Close spacing can be used to obtain windbreak benefits quickly, but thinning ( individual or whole tree row removal ) should be planned to extend the effective life of the windbreak. At general spacing xix guideliness for windbreak dense conifer trees and shrub rows should planned/placed at windward direction and at inner places deciduous tree row and at leeward direction again dense conifer and shurb rows should be placed. The most important property at general spacing guideliness is the maximize the species. The typical windbreak has several components ;. Dense conifer trees to reduce wind velocity.. Tall broud leaf or conifer trees to extand the area of protection. Low shrubs to trip snow, provide wildlife habitat and provide aesthetic value. Figure illustrates a recommended windbreak design 4. Presipitation and Humidity Control Various parts of plants intersept presipitation and thus are able to modify or control climate, trees and shrubs tend to couse an increase to prestipitation above them. Leaf surfaces cause excess transpiration of water from the soil through the plant into the atmosphere immediately above the plant. Moisture reacting the earth through a shruber tree canopy is retained longer than moisture falling upon exposed soil. The ability of plants to intercept presipitation and slow it down helps to control surface water run off and resulting soil erosion. The protection from sun and wind provided by plants. Reduces evoporation of soil water. Fog condenses on the needles of conifers on the upper and lower surfaces of leaves on deciduous trees. This condensation of fog than falls to the earth as drig water from the various parts of the plant. In addition plants can control snow drifting and snowfalls. Generally snow is held on the leaves, branches, or needles of trees. Snow is retained on the trees longer than rain therefore, trees withhold moisture for a longer period, allowing some to fall as large masses before melting and some to fall as it melts. This maybe observed after a heavy snowfall in a forest. 5. Temperature Control Temperature control is linked directly to and is a result of solar radiation control, wind control and precipitation control. Plants used for the temperature control have the greatest effect by moderating temperatures near the ground. Deciduous trees are good temperature control devices if we compare with the needle trees, in that they cool in summer and yet allow winter sun to pass through. Vines on xx walls or trellises are also some of nature's automatic leafe control devices cooling by evoporation and providing shade. Where there is free air movement, there is little or no difference between air temperaures in sun or shade. However, under trees flanked shrubs reflecting air currents upward there will be cooller temperatures in the the shade. An evergreen or row of evergreens placed next to a wall create an area of " dead" air between plants and wall. This acts much the same as the dead air space in the wall of a house. The temperature gradient between the inside of the building and the dead air space is reduced and held relatively constant, thus preventing the escape of heat from the building. Retrofitting to insure a greater amount of solar energy reaching the site, remove any coniferous (needled evergreen) or ericaceus (broad-leaved evergreen) trees from the south or south east of the dwelling unit. Those on the south west may be removed, thinned or replaced depending on the precise climate situation on the site. Each conditional area have different needs to provide comfort for users. As a result, in the cold area we have to create temperature to reduce energy corruption with mechanical heatinh. We have to provide moisturation for create comfortable spaces in the arid area, in the other hand, natural elements are used for provide microclimate to reduce increasing moisturation in the moisturation area. According to this study, in Istanbul which has temperate-humid climate characteristic, Bağdat caddesi along the street, I. Levent settlement area in seperate order and Ataşehir in free order, where examined as per plantation impact upon climate comfort. In spite of modifying Bağdat Caddesi and Ataşehir according to climate comfort, positively it may be said that plantation surrounding building in I. Levent was planned /planted taking base of visiual and aesthetic value. The climate condition which effects human productivity with a major range, is partly possible by using plants. So to create climate comfort conditions at livable level for user will possible by planning /designing whole areas surrounding buildings and open public spaces by professional authorities who are interested in climate control with plantation
Climate Control With Plantation As An Urban Design Element
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1998
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1998
Keywords: Bitkilendirme; Kentsel tasarım; İklimlendirme; İstanbul-Ataşehir; İstanbul-Bağdat Caddesi; Planting; Urban design; Air conditioning; İstanbul-Ataşehir; İstanbul-Bağdat Caddesi